Soil Sampling Procedures - Davie Kadyampakeni; Kelly Morgan; Arnold Schumann; Rhuanito Ferrarezi; Jamie D Burrow (EDIS, 2020)
To achieve optimal grove nutrition, citrus growers must test grove soil before beginning any fertilization program. Standard procedures for sampling, preparing, and analyzing soil should be followed for meaningful interpretations of the test results and accurate recommendations. This new two-page fact sheet, published by the UF/IFAS Department of Soil and Water Sciences, provides illustrated soil sampling procedures and tables to aid in basic interpretation of lab results. Written by Davie Kadyampakeni, Kelly Morgan, Arnold Schumann, and Rhuanito S. Ferrarezi. https://edis.ifas.ufl.edu/ss667